Environmentally and socially responsible global production and trade of timber and tree crop commodities: certification as a transient issue-attention cycle response to ecological and social issues - Leimona, B.; Noordwijk, M. van; Mithöfer, D.; Cerutti, P.O. (Informa UK Limited, 2017)
The Sustainable Development Goal (SDG) number 12 of Agenda 2030 states that the world ‘requires a strong national framework for sustainable consumption and production, integrated into national and ...